THE EFFECTS OF ADHESIVE TYPE AND CONCENTRATION IN THE MANUFACTURING OF FILTER CAKE BRIQUETTES AS AN ALTERNATIVE FUEL - Andes Ismayana dan Moh. Rizal Afriyanto (Department of Agroindustrial Technology, Bogor Agricultural University, 2011)
ABSTRACTThe objective of this study was to determine the effects of adding the type and concentration of an appropriate adhesive material in the manufacturing of filter cake briquettes. This study was conducted by making briquettes using different adhesive materials, i.e. molasses and tapioca with adhesive levels of 10%, 15%, and 20% for each adhesive material. The results showed that the addition of adhesive will increase the density , decrease the rate of combustion , and increase the calory of briquettes from 1026 calories/gram to 1995 calories/gram. The resulting coal of filter cake briquettes were good enough by generating coals temperatures between 357 and 496°C. In addition, this filter cake briquettes produced low ash content and flying substances levels higher than those of wood charcoal briquettesin the market.Keywords: filter cake briquette, tapioca, molasses, value of calories, coals temperature